The impact of physical and socio-cultural factors on structuring vernacular dwellings in Eastern Black Sea Region - Onur, Dilara; Ziyrek, Burcu Efe; USTA, GÜLAY (My University, 2012)
People live in their physical and social environments and they ought to arrange their relations via physical and social environments surrounding them to meet sheltering need, which is their essential requirement. When, especially, traditional residential architecture that represents historical and cultural backgrounds of societies is examined, the critical importance of human-environment relation is observed. When Anatolian traditional residential architecture is examined, it is observed that, as in many societies, dwellings are the reflections of the physical and social structures of the region where they are located. Dwellings that are structured differently in various parts of Anatolia signify both physical conditions and social characteristic and rich cultural background of the region they are located. In this sense, vernacular dwellings in Eastern Black Sea Region have a key position in the Anatolian residential architecture. Within the scope of this study, the impact of physical and social factors on residential architecture was analyzed by focusing on the vernacular dwellings in Eastern Black Sea Region (in Turkey). In this study, structuring process of the vernacular dwellings in Eastern Black Sea Region was examined from the housing scale to the location scale in terms of physical and social factors.
Keywords: Geleneksel konut; Eastern black sea region; vernacular dwelling; natural and physical factors; socio-cultural factors